2020
DOI: 10.3350/cmh.2019.0001n
|View full text |Cite
|
Sign up to set email alerts
|

Application of transient elastography in nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is currently the most common chronic liver disease worldwide. Although it has become one of the leading causes of cirrhosis and hepatocellular carcinoma in the Western world, the proportion of NAFLD patients developing these complications is rather small. Therefore, current guidelines recommend noninvasive tests for the initial assessment of NAFLD. Among the available non-invasive tests, transient elastography by FibroScan<sup>®</sup> (Echosens, Paris, Franc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 99 publications
(127 reference statements)
0
80
0
4
Order By: Relevance
“…It is clear that the NLCSP warrants further improvement. 15,16 Inclusion of these patients should be considered for the first candidate group when expanding the NLCSP. In terms of the target group identification process, none of the three suggestions for improving the surveillance target selection process achieved high agreement rates (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that the NLCSP warrants further improvement. 15,16 Inclusion of these patients should be considered for the first candidate group when expanding the NLCSP. In terms of the target group identification process, none of the three suggestions for improving the surveillance target selection process achieved high agreement rates (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…CAP and LS measurement were performed on the right lobe of the liver through the intercostal spaces with subjects lying in the dorsal decubitus position with the right arm in maximal abduction by one experienced technician who was blind to the subjects' clinical data 9 . An experienced technician (>10 000 examinations) from each institute who was blinded to the patients’ clinical data performed all LS and CAP measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Transient elastography (Fibroscan ® ) is an accurate, noninvasive, simple machine to measure the degree of fibrosis and is easy to repeat 9,10 . Therefore, Fibroscan ® has been used as a useful tool for monitoring fibrosis improvement after antiviral treatment in CHB patients 10‐15 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been thought that the cut-off values for the XL probe should be lower, around 1.5–2 kPa, than the ones used for the standard M probe [ 35 , 40 , 68 , 96 , 97 ]. However, in a novel prospective study [ 65 ], Wong et al found that the same LS cut-off values can be used for both M and XL probe in clinical practice, when used in patients with BMI <30 kg/m 2 and ≥30 kg/m 2 , respectively, as the high BMI independently increases liver stiffness values [ 98 ].…”
Section: Liver Parenchyma Characterization In Nafld Patients With mentioning
confidence: 99%